Genotype–Phenotype Correlation Analysis and Identification of a Novel SRD5A2 Mutation in Four Unrelated Chinese Patients with 5α-Reductase Deficiency - Gui, Ting; Yao, Fengxia; Yang, Xinzhuang; Wang, Xi; Nie, Min; Wu, Xueyan; Tian, Qinjie (International journal of general medicine, 2022)
The 5α-reductase type 2 deficiency is mainly caused by mutations in the SRD5A2 gene. Our study aims to investigate the SRD5A2 gene mutations and their corresponding manifestations.ObjectiveThe 5α-reductase type 2 deficiency is mainly caused by mutations in the SRD5A2 gene. Our study aims to investigate the SRD5A2 gene mutations and their corresponding manifestations.Four unrelated Chinese patients with 46, XY ambiguous genitalia were studied. Molecular genetic alterations and clinical presentations were analyzed.MethodsFour unrelated Chinese patients with 46, XY ambiguous genitalia were studied. Molecular genetic alterations and clinical presentations were analyzed.Five variants in the SRD5A2 gene were identified, all highly conserved in vertebrate orthologs. The p.P251A was a novel variant, predicted to "Affect protein function" and to be "probably damaging". Combining patients' gene mutations with their external genitalia and male sexual characteristics, we found that three variants, p.Q6X, p.N193S, and p.H90Y, were associated with severe undervirilization of external genitalia, and the other two, p.G203S and p.P251A, probably retained part of the enzyme activity.ResultsFive variants in the SRD5A2 gene were identified, all highly conserved in vertebrate orthologs. The p.P251A was a novel variant, predicted to "Affect protein function" and to be "probably damaging". Combining patients' gene mutations with their external genitalia and male sexual characteristics, we found that three variants, p.Q6X, p.N193S, and p.H90Y, were associated with severe undervirilization of external genitalia, and the other two, p.G203S and p.P251A, probably retained part of the enzyme activity.Mutation analysis of SRD5A2 gene is crucial for differential diagnosis in patients with 5α-reductase type 2 deficiency. Patients' variable manifestations depend on the mutation type and residual enzyme activity. The novel variant p.P251A enlarges the spectrum of SRD5A2 mutations.ConclusionMutation analysis of SRD5A2 gene is crucial for differential diagnosis in patients with 5α-reductase type 2 deficiency. Patients' variable manifestations depend on the mutation type and residual enzyme activity. The novel variant p.P251A enlarges the spectrum of SRD5A2 mutations.